Perception on Desa Melayu apartment society towards Johor food heritage - Harun, Hairuddin; Mohd Zaini, Nurul Syahirah (Penerbit UTHM, 2021)
Along with the rapidly growing economy and increasing population community in Johor like other states in Malaysia, Malay Modern society, especially the generation now gradually abandon the Johor food Heritage due to the pursuit of modern and viral food that available in the market today. Unlimited social and information technology shifts are believed to influence changes in their food intake also. Loss of interest, no early exposure to traditional food and the attitude of glorifying foreign food is considered a contributor towards the extinction of this special dish (Pakar Makanan Warisan Negara, 2019)